TEXT â€“ ART FOR LISTENERS - Gagoshidze, Tamar (European Scientific Journal, ESJ, 2014)
Since the last century, the text is understood as a poly-semiotic structure. For example, P. Sergio, based on French experience, offers the list 136comprising eight formed components; that is the idea of â€œdiscourseâ€ in the text related to theory is already ambiguous. We can identify three main determinants of â€œdiscourseâ€ based on different cultures and thoughts. In the linguistic context, the term was first coined by American scientist Z. Harris in his article â€œDiscourse Analysis137â€. However, the broad application of the term was acquired twenty years later. In the world of linguistics, discourse is defined as a speech, text, dialogue, which is an integral part of communicational case. Thus, discourse is countering the text both dynamically and statically. The understanding of the term by French Structuralists and Post-Structuralists is indicated through works by M. Foucault 138and his followers. According to the scientists, discourse equates the style of speech, the manner and carries individualistic qualities (political discourse, teachersâ€™ discourse, the authorsâ€™ style as discourse). This vision represents discourse in a social color.